INNOVATION OF TAFSIR LEARNING METHODS IN DAYAH ACEH - Anshari, Ismail; Tihalimah, Tihalimah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
Dayah is considered an institution that builds an essential base for developing education in Indonesia. In recent years, the quantity has increased, especially in Nanggroe Aceh Darussalam, Indonesia's westernmost province. However, a big problem still arises here, and the dayah needs more learning methodology in some Islamic sciences, especially in interpreting the Qur'an. This study aims to examine the interpretation learning methods practiced so far in the dayah and simultaneously offer solutions to the interpretation learning methods in the Aceh Dayah. Using descriptive qualitative research, it can be concluded that the teaching methods used by dayahs in Aceh are still classic, for example, the wetonan (bandungan), sorogan, memorization, and discussion methods. In this article, the authors offer new learning strategies such as discovery or inquiry-discovery, mastery, integrated learning methods or integrated learning, and reception learning strategies. It is hoped that this learning method will encourage the dayah toward constructive development for the future of Islam